The Influence of Phonetic Exercises and Games in Russian Language Lessons on the Cognitive Universal Learning Activities of Students - Dedakhanov, Abumalik Mutallievich (Web of Scientist International Scientific Research Journal, 2025)
This article highlights the importance of phonetic exercises and games in Russian language lessons in the formation of students' cognitive universal learning activity. Based on experimental work conducted at the clarifying, formative and final stages, it is scientifically substantiated that phonetic games have an effective effect on the development of phonetic perception, speech activity, logical thinking and independent thinking skills in students. It also reveals the potential of phonetic exercises and games in the formation of motivational, cognitive, communicative and regulatory components. The results obtained indicate the need for the systematic use of phonetic games to increase the effectiveness of mastering the Russian language in primary school students.